IMPACT OF HYPERTENSION ON INTRAOPERATIVE BLOOD DURING SPINAL ANESTHESIA IN ORTHOPEDIC SURGERY (Pakistan Journal of Medical & Cardiological Review, 2026)
Background: Hypertension is a common comorbidity in orthopedic surgery. Because of its sympatholytic and hemostatic effects, spinal anesthesia is a preferred method of anesthesia for orthopedic surgery. However, it is linked to significant hemodynamic changes, which may be exacerbated in hypertensive patients because of long-term alterations in vascular reactivity, endothelial function, and hemostasis. Although the effects of hypertension on the cardiovascular system are well documented, little is known about how hypertension affects intraoperative blood loss during orthopedic spinal anesthesia. This study aimed to examine the estimated blood loss (EBL) in patients with hypertension and those with normotension after orthopedic surgery under spinal anesthesia.Methods: This quantitative descriptive comparative observational study was conducted at the Combined Military Hospital and Social Security Hospital in Lahore, Pakistan. 120 patients were recruited by purposeful sampling; 60 of them were placed in Group A (controlled hypertension) and 60 in Group B (normotensive). Volumetric aspiration and sponge gravimetry were used to measure EBL at 60, 120, and wound closure. Systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), and SpO₂ were recorded both prior to and following spinal injection. In SPSS v25, descriptive statistics and the independent samples t-test (Levene's test for equality of variances) were used for analysis.Results: At all intraoperative time points, hypertensive patients exhibit significantly higher estimated blood loss than normotensive patients: at 60 minutes (mean 3.97 vs. 3.08, p =.000), at 120 minutes (3.63 vs. 2.72, p =.000), at wound closure (2.98 vs. 2.13, p =.000), and total EBL (3.40 vs. 2.63, p =.000). The majority of patients (46.7%) had a total EBL of 400–499 mL, with a higher percentage of hypertensive patients having larger volumes. Hemodynamics varied significantly after spinal, with 25% of patients needing vasopressors and 4.2% of patients having severe hypotension (SBP < 80 mmHg). All blood loss factors had statistically significant differences, according to independent samples t-tests.Conclusion: In orthopedic surgery performed under spinal anesthesia, hypertension is a significant and independent predictor of intraoperative blood loss. Even in patients with treated hypertension, the vascular and hemostatic dysfunction of chronic hypertension results in increased blood loss. For hypertensive patients undergoing orthopedic surgery, this study emphasizes the necessity of patient-specific blood conservation strategies, such as preoperative hemoglobin optimization, antifibrinolytic medication, vasopressor availability, and thorough hemodynamic monitoring during surgery.